2011
DOI: 10.4028/www.scientific.net/amm.110-116.431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGR on the Exhaust Gas Temperature and Exhaust Opacity in Compression Ignition Engines Using Jatropha Oil as Fuel

Abstract: Diesel engines are widely used as power sources for medium and heavy-duty applications because of their lower fuel consumption and lower emissions of carbon monoxide (CO) and unburned hydrocarbons (HC) compared with gasoline engines. Efficient use of natural resources is one of the fundamental requirements for any country to become self-sustainable. Both in organized and unorganized sectors internal combustion engine has become an indispensable prime mover. With the increasing demand on the use of fossil fuels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The reason for this is poor atomization and lack of oxygen at higher loads. 41 The HC emissions were decreased with the addition of biodiesel to diesel fuel. 42 The amount of reduction in HC emission compared to neat diesel is 14.63%.…”
Section: Carbon Monoxide (Co)mentioning
confidence: 99%
“…The reason for this is poor atomization and lack of oxygen at higher loads. 41 The HC emissions were decreased with the addition of biodiesel to diesel fuel. 42 The amount of reduction in HC emission compared to neat diesel is 14.63%.…”
Section: Carbon Monoxide (Co)mentioning
confidence: 99%
“…In the study, the smoke was increased to a high level when EGR was used, causing reduced oxygen inthe combustion chamber compared to a diesel engine and increasing the CO emission level. A study by Avinash Kumar et al [7] on a CI engine with EGR fuelled with diesel to investigate the effects of different EGR charges on the exhaust emission from the engine demonstrated an effective system; however, the increase in specific fuel consumption (SFC) was observed by 10-15%, whereas the EGR system had reduced NOx emission. Moreover, a study by Hussain et al [8] conducted on a four-stroke, two cylinders diesel engine at a constant speed of 1500 rpm showed that the use of EGR had reduced the unburned hydrocarbon (UHC).…”
Section: Introductionmentioning
confidence: 99%